Histopathological Features of Group E Retinoblastoma Eyes after Upfront Enucleation: Doi:10.36351/pjo.v36i4.1057 - Viyani, Usman; Mughal, Jamal; Arshad, Muhammad Owais; Javed, Anum; Nasir, Javeria; Chatni, Muhammad Hanif (Pakistan Journal of Ophthalmology, 2020)
Purpose: To study histopathological features of eyes with intraocular Group E retinoblastoma primarily treated by enucleation at a tertiary care centre in Karachi, Pakistan. Study Design: Retrospective histopathological study. Place and Duration of Study: Department of Ophthalmology, Patel Hospital, Karachi, January 2012 to August 2019. Methods: Seventy five eyes of children diagnosed with Group E retinoblastoma, on clinical examination, examination under general anaesthesia along with MRI and then enucleated were examined histopathologically after being primarily enucleated. Histological features were enlisted for the presence of choroidal invasion, extent of optic nerve invasion, anterior chamber involvement, scleral and extra-scleral invasion along with tumour differentiation. Demographic variables (age at presentation, gender, laterality of the disease, median follow-up) and the histopathological features of tumour along with high risk features were assessed using SPSS version 24. Results: Out of 75 eyes, 48 (64%) eyes showed high risk histopathological features including post lamina cribrosa involvement, choroidal invasion, scleral involvement, anterior chamber involvement (angle, iris, ciliary body). All high risk features were significantly more in the poorly differentiated group of tumours. All patients showing high risk features were given post enucleation systemic chemotherapy accordingly. Conclusion: By identifying the histopathological pattern and high risk features, we can decrease the chances of metastasis, recurrence, mortality and morbidity of these children which pose an overwhelming physical, psychological, social and financial burden on our society as a whole. Further large, multi-centre prospective studies can provide with a better understanding about the high risk features and histopathological patterns of retinoblastoma in our region. Key Words: Retinoblastoma, Enucleation, Chemotherapy.